Modulation of spatiotemporal dynamics in the bromate–sulfite–ferrocyanide reaction system by visible light. Issue 24 (18th May 2022) - Liu, Mengfei; Meng, Chunxiao; Yuan, Ling
Abstract : The BSF reaction system displayed photoinduction and photoinhibition behavior under flow conditions. The oscillatory period decreased as the light irradiation mainly enhanced the negative process and affected the positive feedback. Abstract : We have carried out the first systematic study of the effects of visible light on the homogenous dynamics in the bromate–sulfite–ferrocyanide (BSF) reaction. Under flow conditions, the reaction system displayed photoinduction and photoinhibition behavior, and the oscillatory period decreased with the increase of light intensity, which is due to the fact that light irradiation mainly enhanced the negative process and affected the positive feedback. The light effect on positive and negative feedback is studied by analyzing the period length of pH increasing and decreasing in detail. With the increase of light intensity, the period length of pH increasing decreases monotonically, while the period length of pH decreasing changes nonmonotonically. These results suggest that light could be used as a powerful tool to control homogenous dynamics. Results obtained from numerical simulations are in good agreement with experimental data.